Association between Lymphovascular Invasion and Carcinoembryonic Antigen as a Prognostic Factor in Post Colorectal Cancer Surgery Patients: Literature Review - Yossi Andila; Muhammad Al Anas (JURNAL IMPLEMENTA HUSADA, 2026)
Background: Several prognostic factors have been proposed to reflect the course of the disease, such as demographic, histopathological, immunological, molecular and multidisciplinary interventions. Histological examination is widely used to predict prognosis and optimize adjuvant treatment, such as LVI and CEA.Purpose and objectives: This study is a literature review that aims to see the correlation of LVI and CEA as a postoperative porgnostic indicator which is a development from previous studies regarding CEA levels on chemotherapy responseMethods: This study was a literature review focusing on the association between lymphovascular invasion and carcinoembryonic antigen as prognostic factors in post-colorectal cancer surgery patients. Two authors independently conducted searches of the PubMed, ScienceDirect, and British Medical Journal databases to identify relevant studies. Selected articles were reviewed and analyzed to synthesize current evidence on the topic.Results: CEA normalized in more than 70% of patients after surgery, and the outcomes of patients with postoperative CEA who returned to normal were similar to those with normal preoperative CEA. Lymphovascular invasion is an independent poor prognostic marker for survival in colorectal cancer. Node negative patients, particularly stage II, are the most important group that could benefit from identification of LVI.Conclusion: Serum CEA and LVI levels have the potential to be better biomarkers for the prognosis of colorectal cancer patients.